1986
DOI: 10.1099/00221287-132-9-2421
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Composition of Azole-sensitive and Azole-resistant Strains of Candida albicans

Abstract: The lipid compositions of two azole-sensitive (A and B2630) and two azole-resistant (AD and KB) strains of the opportunistic fungal pathogen Candida albicans were studied by using several lipid extraction procedures: no differences were observed between the lipid content or total phospholipid/neutral lipid ratios of the four strains. All contained phosphatidylethanolamine, phosp hatidylc holine, phosphatid ylinosi to1 and p hosp hat id ylserine as major phospholipids, with smaller amounts of phosphatidylglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 38 publications
5
76
0
Order By: Relevance
“…It has been shown that some of the azole-resistant C. albicans isolates exhibit altered membrane phospholipid and sterol compositions (15,23,30). Such lipid changes are observed both in clinical and in in vitro-adapted azole-resistant isolates of C. albicans (16,17,23,30). We as well as others have observed that Cdr1p and Pdr5p are sensitive to fluctuations in the lipid environment, where functions mediated by these drug extrusion pumps are selectively affected (19,47).…”
mentioning
confidence: 88%
“…It has been shown that some of the azole-resistant C. albicans isolates exhibit altered membrane phospholipid and sterol compositions (15,23,30). Such lipid changes are observed both in clinical and in in vitro-adapted azole-resistant isolates of C. albicans (16,17,23,30). We as well as others have observed that Cdr1p and Pdr5p are sensitive to fluctuations in the lipid environment, where functions mediated by these drug extrusion pumps are selectively affected (19,47).…”
mentioning
confidence: 88%
“…Since altered lipid composition (e.g. alteration in sterol levels) is known to be a mechanism of resistance in planktonic Candida cells (Hitchcock et al, 1986;Mago & Khuller, 1989) as well as in Candida biofilms (Mukherjee et al, 2003), it is possible that the increase in unsaturated index in Candida biofilms (of early phase) may contribute to alterations in membrane fluidity, biofilm maturation and resistance against antifungal agents. Our studies also revealed that the PC : PE ratio increased during biofilm maturation, along with a decrease in acyl unsaturation, which may indicate a reduction in the propensity of the membrane to undergo a transition to hexagonal phase (non-bilayer), a feature that may relate to the attachment of the biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans (serotype A; NCPF 3153) was maintained on Sabouraud's dextrose agar (Oxoid) and grown in Sabouraud's dextrose broth (Oxoid) essentially as described by Hitchcock et al (1986). Under these conditions the organisms grew exclusively in the yeast phase.…”
Section: K Dickinson a N D Othersmentioning
confidence: 99%